PENERAPAN LAPORAN KEUANGAN BERBASIS WEBSITE PADA USAHA JASA MULTIMEDIA LOF VISUAL - Wangarry, Andreas Randy; Syaefudin, Fanesa Isalia Minanda; Paendong, Yelly Sjenny; Wagiu, Decire Dumingkan; Pangemanan, Shane Anneke (Jurnal Riset Terapan Akuntansi, 2025)
The Lof Visual Multimedia Services Business is a type of MSME in the service sector that is very open to making changes to make this business better as technology develops. The research objective is to apply website-based financial reports to the Lof Visual Multimedia Services Business. The type of research is qualitative research. Data collection methods through interviews and documentation. The result of this research is a website-based financial reporting application that is capable of managing transaction data, carrying out automatic journaling, and producing financial reports: Profit and Loss Report, Financial Position Report and CaLK in real-time. By implementing this system, Lof Visual can present financial reports that are accurate, timely and easy to access. This research provides a real solution that directly transforms Lof Visual's business processes from manual to digital. The solution for using this website is to significantly increase operational efficiency, reduce the risk of human error in recording, and most importantly, present real-time financial data for more accurate and data-based decision making. Keywords: Accounting Information Systems, Financial Reports, MSMEs, SAK EMKM, Websites.